The contemporary debate over Latin American Studies - López Nájera, Verónica Renata (2007)
The author examines the current state of contemporary Latin American theories through their manifestation in the field of knowledge and the lines of investigation that are developed in the post graduate course in Latin American Studies in Mexico. In order to do this, she revises the development of Postcolonial Studies, Subaltern Studies and Cultural Studies.